(untitled) (Research, Society and Development, 2023)
Introduction: In light of the COVID-19 pandemic, Systemic Arterial Hypertension was identified as one of the chronic diseases that pose a high risk of developing a severe form of the disease and as one of the biggest challenges for monitoring in Primary Care. The lack and/or reduction of consultations due to the need to minimize the risks of contagion from COVID-19 and the potential complications that it can cause in this population also becomes a problem in the intervention of care, treatment, and quality of life. Objective: To understand the perception of self-care among people with SAH in the face of the COVID-19 pandemic. Methodology: This is qualitative, exploratory, and descriptive research carried out at the Family Health Strategy (ESF) in the city of Barrocas, Ba. The study participants were 06 people with SAH who attend the ESF and are registered in the Hiperdia program. The data collection technique and instrument were, respectively, the semi-structured interview and the characterization script, with the data analyzed using the Bardin Content Analysis method. Results: quality of life, perception of self-care and the impact of the pandemic on this care were discussed. Final considerations: It was possible to understand that the self-care of people with SAH was interfered with by the pandemic due to the need to face changes in lifestyle through social isolation and suffer interruptions in continued care in primary care, and highlight the importance of comprehensive monitoring of individuals in PHC to promote self-care.